The principle of the joint line restoring in revision knee replacement - D.N. Efimov; N.S. Nikolaev (Известия высших учебных заведений. Поволжский регион: Медицинские науки, 2023)
Background. The need for revision knee replacement is increasing every year. Technical difficulties are the determination of the correct level of the joint line in case of femoral defects. The purpose of the study is to determine the average coefficients of the joint line distalization. Materials and Methods. The parameters of the knee joint determined by X-ray were studied. Based on these parameters, the coefficients of the relationship of anatomical structures depending on gender were determined. Results. Using these data, the average coefficients of the joint line distalization were obtained. Conclusions. The proposed method for determining the joint line distalization is universal, since the studied parameters are relative, which makes it possible to level the error between them when measuring the studied values by the X-ray method and during the surgical intervention.